2012
DOI: 10.1590/s1516-05722012000400006
|View full text |Cite
|
Sign up to set email alerts
|

Substratos, concentrações de ácido indolbutírico e tipos de miniestacas no enraizamento de melaleuca (Melaleuca alternifolia Cheel)

Abstract: RESUMO:Melaleuca alternifolia tem como produto principal o óleo essencial extraído das folhas devido às propriedades antifúngicas e antibacterianas. Pouco se tem relatado sobre a propagação desta espécie, sendo a miniestaquia uma alternativa para a propagação vegetativa de clones superiores visando à implantação de campo de produção. ), em dois tipos de miniestacas (apical e mediana). As miniestacas foram confeccionadas com 5 cm de comprimento, mantidas em casa de vegetação com nebulização intermitente, e, apó… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 6 publications
1
9
0
4
Order By: Relevance
“…Thus, as previously mentioned, the concentration of 4000 mg L -1 produced significantly improved results for the number and length of the roots; however, since the lower concentration (1000 mg L -1 ) did not yield significantly different results from those with the highest concentration, it is more economically viable to apply a smaller amount of phytoregulator to the base of the minicuttings of Luehea divaricata. A similar result to the one obtained in the present study was observed with Melaleuca alternifolia, which presented an average root length of 10.47 cm with the use of a higher concentration of IBA at 2000 mg L -1 (OLIVEIRA et al, 2012). In the minicuttings of Handroanthus heptaphyllus, a shorter average root length than that observed in this study was obtained (4.47 cm) by applying a much higher concentration (8000 mg L -1 ) of IBA (OLIVEIRA, et al, 2016).…”
Section: Resultssupporting
confidence: 91%
“…Thus, as previously mentioned, the concentration of 4000 mg L -1 produced significantly improved results for the number and length of the roots; however, since the lower concentration (1000 mg L -1 ) did not yield significantly different results from those with the highest concentration, it is more economically viable to apply a smaller amount of phytoregulator to the base of the minicuttings of Luehea divaricata. A similar result to the one obtained in the present study was observed with Melaleuca alternifolia, which presented an average root length of 10.47 cm with the use of a higher concentration of IBA at 2000 mg L -1 (OLIVEIRA et al, 2012). In the minicuttings of Handroanthus heptaphyllus, a shorter average root length than that observed in this study was obtained (4.47 cm) by applying a much higher concentration (8000 mg L -1 ) of IBA (OLIVEIRA, et al, 2016).…”
Section: Resultssupporting
confidence: 91%
“…This is an indication that root formation occurred in these seedlings even after 35 DAC, thus allowing the seedling to complete its development. Callus and roots formation are independent processes in most plants (GOULART et al, 2014), but in some of them, callus formation can be a precursor to the formation of adventitious roots (GOULART et al, 2014;OLIVEIRA et al, 2012). For., Piracicaba, v. 47, n. 122, p. 336-345 In species with difficult rooting, the substrate can influence both the rooting percentage and the quality of the formed root system (XAVIER; WENDLING; SILVA, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The types of mini-cutting did not influence the rooting of Handroanthus heptaphyllus (Freitas et al, 2016) and Toona ciliata (Ferreira et al, 2012). Yet, in Anadenanthera macrocarpa (Dias et al, 2015), Melaleuca alternifolia (Oliveira et al, 2012), and Peltophorum dubium (Mantovani et al, 2017) apical mini-cuttings were superior for rooting.…”
Section: Types Of Mini-cutting and Leaves In The Rhizogenesis Of Paramentioning
confidence: 89%